Energy consumption and total factor productivity growth in Iranian agriculture - Reza Moghaddasi; Amene Anoushe Pour (Energy Reports, 2016)
In this study we investigated the relation between energy consumption and growth of total factor productivity (TFP) of agriculture in Iran from 1974 to 2012 using Solow residual method. The results from estimated aggregate Cobb-Douglas production function showed that one percent change in the value of labor, capital and energy will lead to 4.07, 0.09 and 0.49 percent change in agriculture value added, respectively. Also in a long term, based on the Johansen cointegration test, there is a negative relation between TFP growth and energy consumption in Iranian agriculture which might be due to cheap and inefficient energy use in this sector. Gradual liberalization of energy price and use of so called green box support policies is recommended.
Keywords: 330; Energy consumption; Agriculture; Iran; Total factor productivity